Joint-stock company as a form of municipal management in the field of environmental protection infrastructure by local government units. Selected issues of organization and functioning of the bodies of a joint-stock company - Rudnicki, Maciej (Studia Ecologiae et Bioethicae, 2003)
Abstract in English is not available for this article.